2007
DOI: 10.1007/s00122-007-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and allelic dosage effect of Hwc1, a complementary hybrid weakness gene in rice

Abstract: Hybrid weakness is a reproductive barrier that is found in many plant species. In rice, the hybrid weakness caused by two complementary genes, Hwc1 and Hwc2, has been surveyed intensively. However, their gene products and the molecular mechanism that causes hybrid weakness have remained unknown. We performed linkage analyses of Hwc1, narrowed down the area of interest to 60 kb, and identified eight candidate genes. In the F(2) population, in which both Hwc1 and Hwc2 genes were segregated, plants were separable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…This reduced activity of the SAM should be one of the reasons for the short stature of the NJF 1 plants. It was reported that homozygotes for Hwc1 and Hwc2 showed a severe weakness and very small shoots and did not develop roots (Ichitani et al 2007). Thus, the genes responsible for this type of hybrid weakness may also be involved in the SAM maintenance and not only in the RAM maintenance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This reduced activity of the SAM should be one of the reasons for the short stature of the NJF 1 plants. It was reported that homozygotes for Hwc1 and Hwc2 showed a severe weakness and very small shoots and did not develop roots (Ichitani et al 2007). Thus, the genes responsible for this type of hybrid weakness may also be involved in the SAM maintenance and not only in the RAM maintenance.…”
Section: Discussionmentioning
confidence: 97%
“…To reveal the molecular aspect of F 1 HW, the causal genes should be cloned and the 'mutation' by which the genes cause F 1 HW should be determined. Hwc1 and Hwc2 have already been fine-mapped (Ichitani et al 2007) and they are expected to be cloned. When these causal genes of F 1 HW are fully identified, it may become possible to elucidate the mechanisms where by high temperature treatment enabled to rescue the hybrids from weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis for hybrid lethality has been conducted in some plant species, including rice (Ichitani et al 2007;Kuboyama et al 2009), wheat (Mizuno et al 2010), cotton (Song et al 2009), and A. thaliana (Bomblies et al 2007). In these species, hybrid lethality is caused by the interaction between two dominant complementary genes from parental plants.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid in-viability (or weakness) and hybrid sterility have been observed in inter-specific as well as in intra-specific crosses [2,3,4,5,6,7,8,9,10], while hybrid breakdown has been reported only in intra-specific crosses [2,11,12,13,14]. By using molecular linkage maps, some of the genes controlling reproductive barriers have been located on several chromosomes [8,9,10,12,13,15].…”
Section: Introductionmentioning
confidence: 99%